La experiencia de la paternidad en adolescentes (2015)
ABSTARCT: This article presents the results of a qualitative research which has as objective to identify, by means of the narrations of a group of adolescent fathers, the way they experience the paternity and the meanings surrounding this event. The study was addressed based on a historical-hermeneutic approach. The group have 10 male adolescents who were fathers recently and participated in interactive sessions and biographical interviews. The results show that the experience of adolescent paternity is not conceived as a tragic event, this event involves the personal resources of the adolescent to face the challenges derived from early paternity. To be an adolescent father becomes an ambiguous experience: although the adolescent associate this mentally with adult manhood, this experience goes against the adolescent aim of liberty, conquest and rivalry.